Spermatological Parameters In Vitro of Holstein Bulls and Relationship with Male Fertility - Halil Dönmez; Muhammed Enes İnanç (Acta Scientiae Veterinariae, 2024)
Background: The main purpose of evaluating spermatological parameters is to assess the relationship between semen quality and fertility. Extensive research is currently being conducted on freezing, storage, and thawing of bovine semen. Therefore, it is crucial to assess the quality of frozen semen. The freezing of semen causes different degrees of damage to the sperm cell. damages reduce the ability of the spermatozoon to fertilize the oocyte. The ability of sperm to fertilize oocytes is reduced by this damage. This study aims to determine the relationship between fertility and spermatological parameters of frozen-thawed bull semen routinely used in artificial insemination (AI). Materials, Methods & Results: Frozen semen samples from 5 different imported Holstein bulls (5 different collection dates) and 175 cows 2-4 years of age were used. These bulls are commonly used by AI organizations in breeding. Frozen-thawed bull semen straws were analyzed for motility using a phase-contrast microscope with a heated stage, plasma membrane integrity (PMAI), viability, lipid peroxidation level, and mitochondrial oxidative stress were performed with a flow cytometer. PMAI was evaluated by The FITC/PNA-PI double staining protocol, lipid peroxidation level were detected by BODIPY/SYBR 14 double staining protocol; sperm viability was determined using SYBR-14/PI double staining protocol, and sperm mitochondrial oxidative stress was evaluated by MITOSOX/PI double staining protocol. The flow cytometric tests were performed using a CytoFLEX flow cytometer Beckman Coulter equipped with emission filters at 610 ± 20 nm, 585 ± 42 nm, 525 ± 40 nm, and 50 mW (488 nm) laser output. An average of 10,000 spermatozoa were analyzed for each evaluation. Pseudocolor plots were used to compare the side scatter area (SSC-A) with the forward scatter area (FSC-A) of sperm cells to facilitate the selection process. For the AI, cows estrus was confirmed by detecting the graff follicle by rectal palpation and assessing uterine tone. Once clinical and observational signs confirmed estrus, AI was performed. Pregnancy rates were determined 60 days after AI using ultrasound. No significant correlations were found between in vitro spermatological parameters and pregnancy rates (P > 0.05). In one bull, motility scores correlated with pregnancy rate (P < 0.05). There were significant differences in PMAI and mitochondrial oxidative stress parameters (P < 0.05). Positive correlations were found between motility, PMAI, and viability. Furthermore, PMAI was positively correlated with viability and lipid peroxidation levels. Conversely, mitochondrial oxidative stress is negatively correlated with viability and lipid peroxidation. A positive correlation was observed between viability and lipid peroxidation levels. (P ˂ 0.05). No statistically significant difference was observed between the bulls with regard to pregnancy rates. Discussion: Different authors showed a positive correlation between motility and fertility results. Also, flow cytometric results correlated with non-return rate and other spermatological parameters. This study concluded that different organelles and structures within a cell work closely together to carry out metabolic processes. For the accurate prediction and correlation of fertility, it is necessary to create multiple combinations of spermatological parameters. It is also essential to study the associations and correlations between high- and low-fertility bulls and to investigate the pathways leading to their differences. Keywords: artificial insemination, bull, fertility, flow cytometry, spermatological parameters.